The influences of laterite soil towards physico-chemical properties and heavy metals concentration in urban lake quality index - Wan Sulaiman, Wan Syibrah Hanisah; Othman, Rashidi; Hj. Baharuddin, Zainul Mukrim (2018)
The soil is a transmitted agent of water run-off to the water body. Variety of soil type in Malaysia has contributed to the difference of soil properties dissolved in the water and the concern of soil problem in Malaysia involving from laterite, sandy, acid sulfate and organic soil type. Soil properties are one of the subjects of impacting the hydrological composition in terms of physico-chemical properties in a catchment or reservoir including lakes through sediments transportation of pollution that bring all compound result on water quality. Thus, this research aimed to identify the influences of laterite soil towards physico-chemicals properties and heavy metals concentration in urban lake water which can be a benefit in monitoring the water issues in Malaysia. The study was conducted at 10 site studies located at the laterite soil area by taking soil and water samples for further analysis such as physico-chemical properties as well as heavy metals concentrations by using ICP-MS. The results established that the significant physico-chemical and heavy metal variables that strongly associated with laterite soil urban lake are high value in BOD (62.8mg/L), COD (15.87mg/L), NH3-N(0.58mg/L), total suspended solids (59.27mg/L), slightly acidic of pH (6.62) and for heavy metals three elements found dominants in water samples such as Fe (0.49mg/L), Al (0.24mg/L) and Mn (0.05mg/L).The laterite soil samples were dominated by clay (36.1%) whereas the composition of heavy metals concentration was found high in Fe (676.25mg/L), Al (563.13mg/L), and Mn (1.82mg/L). The significant outcome of this study can be used as key tools indicator for monitoring urban lakes status and indices.